Combined Aripiprazole and Electroconvulsive Therapy in a Patient with Treatment-Resistant Schizophrenia and QT Prolongation - Nordin, Muhammad Farhan; Othman, Zahiruddin (Japan International Cultural Exchange Foundation, 2018)
Introduction: Clozapine is regarded as the most effective antipsychotics for patients with treatment-resistant schizophrenia. Of late cardiac safety becomes a principal concern including QTc prolongation that can lead to sudden cardiac death. Objective: This case report will highlight the development of clozapine-induced QTc prolongation, and subsequent stabilization with combined aripiprazole and electroconvulsive therapy (ECT) in a patient with treatment-resistant schizophrenia. Result: We reported a 30-year-old male patient with treatment-resistant schizophrenia who developed QTc prolongation. In 2014, prolonged QTc 521ms was attributed to hypocalcemia. Then in 2016, prolonged QTc 492 ms was noted after the ECT, and most recently QTc 504 ms while on clozapine 100 mg daily. Other investigations including electrolytes, echocardiogram, thyroid, renal and liver function tests were normal. Subsequently, the patient was stabilized on combined aripiprazole and ECT. The QTc ranged 460 to 494 ms while he was on aripiprazole 15 mg daily. Conclusion: The combined use of aripiprazole and ECT is safe for treatment of treatment-resistant schizophrenia with prolonged QTc. Close monitoring is recommended since QTc impact of aripiprazole may be additive to the arrhythmia risk.